The synergic effects of Sc and Zr on the microstructure and mechanical properties of Al–Si–Mg alloy. (25th December 2015) - Xu, Cong; Xiao, Wenlong; Zheng, Ruixiao; Hanada, Shuji; Yamagata, Hiroshi; Ma, Chaoli
Abstract: In order to clarify the possibility of Zr substitution for Sc on the modification of Al-Si casting alloys, the microstructural evolution and tensile properties of Al-Si-Mg based alloys with different combinations of Sc and Zr contents (Sc + Zr = 0.5 wt.%) were systematically investigated. It was found that 0.5 wt.% Sc addition could refine the microstructure significantly and modify the eutectic Si from plate-like morphology to fiber, which promotes the spheroidization of eutectic Si during heat treatment. When Zr was added to partly replace Sc, the microstructure was first further refined, but was then slightly coarsened with increasing Zr content. Moreover, high Zr content was found to decrease its modification on eutectic Si. It was observed that Zr can also concomitantly improve strength and ductility compared with the alloy modified by Sc only. The improvement of mechanical properties was attributed to microstructural refinement, particularly the modification of eutectic Si and precipitation of secondary nano-scale Al3 (Sc1 − x Zrx ) dispersoids. Graphical abstract: The engineering tensile stress–strain curves of T6 tempered F357 based alloys with different combinations of Sc and Zr additions. Note that the F357 alloy with 0.3 wt.% Sc and 0.2 wt.% Zr additions has the best mechanical properties in terms of strength and ductility. Highlights: The combined Sc and Zr additions refined the microstructure and modified the eutectic Si. Tensile properties of F357 alloy were enhanced by Sc and Zr additions. Enhanced ductility is due to modification of eutectic Si and microstructural refinement. The fracture mechanism of Al–Si–Mg modified by Sc and Zr is established.